Challenges in the Additive Manufacture of Single and Multi-Core Optical Fibres. Issue 1 (1st February 2022) - Canning, J.; Chu, Y.; Luo, Y.; Peng, G.D.; Zhang, J.
Abstract: Single and multi-core preforms doped with Bi and Er are fabricated using additive manufacture and drawing into optical fibre. We observe an increasing trend towards shape distortion with increasing number of cores. This is explained by noting that the composite effective softening point falls as the number of doped cores rises. The use of a silica cladding tube elevates the drawing temperature unnecessarily.